1999
DOI: 10.1161/01.cir.100.suppl_2.ii-216
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Gene Expression of Regulators of Myocyte Apoptosis and Myocyte Calcium Homeostasis During Hemodynamic Unloading by Ventricular Assist Devices in Patients With End-Stage Heart Failure

Abstract: Background-In patients with end-stage heart failure, characterized by an increased susceptibility to cardiomyocyte apoptosis and a labile cardiomyocyte calcium homeostasis, a ventricular assist device (VAD) is implanted for bridging to cardiac transplantation and results in myocardial unloading. Although phenotype changes in the failing heart are assumed to result from hemodynamic overload, the reversibility of these changes under unloading is unknown. Methods and Results-By use of quantitative reverse-transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 29 publications
4
63
3
Order By: Relevance
“…Upregulation of Bcl-x L was demonstrated after LVAD, suggesting that susceptibility to apoptosis is decreased upon unloading [115]. Also data from our group support the notion of reduced apoptotic index after mechanical support [108].…”
Section: Apoptosis and Ventricular Unloadingsupporting
confidence: 81%
See 1 more Smart Citation
“…Upregulation of Bcl-x L was demonstrated after LVAD, suggesting that susceptibility to apoptosis is decreased upon unloading [115]. Also data from our group support the notion of reduced apoptotic index after mechanical support [108].…”
Section: Apoptosis and Ventricular Unloadingsupporting
confidence: 81%
“…The myocardial Fas system (APO-1/CD95) was shown to respond very sensitive and promptly to ventricular pressure-and volume changes [114]. After unloading, the expression of the anti-apoptotic protein FasExo6Del is decreased, hence decreased cardiomyocyte susceptibility to apoptosis can be assumed [115].…”
Section: (Extrinsic) Death Receptor Pathwaymentioning
confidence: 99%
“…NF-κB is abundantly detected in the cardiomyocytes of the failing heart and significantly decreases after LVAS support. 34 Altered activity of mitogen activated protein kinase families, such as ERKs, JNK, p38, and Akt, after LVAS support have been reported. 33 These kinases show a sensitivity to mechanical stress of the myocardium and the changes may contribute to the favorable effect of LVAS support on myocardial apoptosis and hypertrophy.…”
Section: Mechanism Of Functional Recoverymentioning
confidence: 99%
“…LVAS unloading resulted in overexpression of the anti-apoptotic proteins, Bcl-2 and Bcl-xL. 32,34 NF-κB is known to be associated with regulation of factors involved in the pathogenesis of CHF, including IL-6, TNF-α, Bcl-XL and hemo-oxygenase-1. NF-κB is abundantly detected in the cardiomyocytes of the failing heart and significantly decreases after LVAS support.…”
Section: Mechanism Of Functional Recoverymentioning
confidence: 99%
“…10,14,18,23 These findings are supported by the reversal of the Bcl-2/Bax ratio in the heart after left ventricular assist device placement. 29 It has been suggested that the cardiac myocyte could also use an alternative apoptotic pathway that activates downstream caspases via "death receptors" (eg, Fas, tumor necrosis factor [TNF] receptor) and caspase-8. 32,37 Expression of the death receptor Fas is upregulated in cardiac myocytes during myocardial ischemia and heart failure, 23,25,37,53 and increased levels of soluble Fas ligand and TNF-␣ have been reported in patients with end-stage heart failure.…”
Section: Regulation Of Cardiac Apoptosismentioning
confidence: 99%